C-Man: Course management assistant - Abd Aziz, Azwan; Yusoff, Nooraini; Siraj, Fadzilah (2006)
Course management systems (CMS) are widely utilized nowadays and their purpose is to provide a teaching and learning environment that includes tools for retrieval of educational content, synchronous and asynchronous communication, administrative functions, and assessment. This project identifies the functionalities of a CMS based on four aspects: course grading, course support material, course notification, and system usability.A prototype called C-Man was built based on the identified functionalities and further tested by potential users to evaluate the prototype usability.The evaluation used Computer System Usability Questionnaire (CSUQ) and was performed according to four subscales of usability namely the system use fulness, the information quality, the interface quality and the overall satisfaction.Overall results showed that majority of the participants satisfied with the C-Man us ability.Nevertheless, for the future enhancements, recommendations from participants will be taken into considerations.